Living Religious Moderation within the Sipakatau, Sipakainge’, and Sipakalebbi Cultures of the Bugis Community - Asni Zubair; Hamzah Hamzah; Satriadi Satriadi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2022)
This study aims to identify indicators of religious moderation in the internalization of Sipakatau, Sipakainge’, and Sipakalebbi cultures among the Bugis community in Mallari Village, Awangpone District, Bone Regency. It employs qualitative research in the form of case studies and interpretive methods. Data collection involves observation and interviews, with the analytical theory of indicators of religious moderation in Indonesia. The findings revealed several indicators of religious moderation in the mentioned cultures. Firstly, Sipakatau culture demonstrates tolerance and the accommodation of local values, as seen in socio-political life, emphasizing respect for political differences and upholding deliberation. Secondly, Sipakainge’ culture is committed to national values, evident through community compliance with village regulations and educational activities aligned with national education orientation. Lastly, the value of humanism is observed in the internalization of Sipakalebbi culture, as reflected in village government policies that empower individuals with disabilities. Theoretical implications suggest that religious moderation can be integrated into local wisdom through socio-political, educational, and cultural activities. However, the study’s limitations include not examining obstacles or challenges in mainstreaming religious moderation within the Sipakatau, Sipakainge’, and Sipakalebbi cultures in Mallari Village.